2008
DOI: 10.1080/08860220802356531
|View full text |Cite
|
Sign up to set email alerts
|

AST-120 Treatment in Pre-Dialysis Period Affects the Prognosis in Patients on Hemodialysis

Abstract: Background/Aims. An oral adsorbent, AST-120, has been shown to retard the deterioration of renal function in patients with chronic kidney disease (CKD) by decreasing serum nephrotoxic substances such as indoxyl sulfate. Recent studies have suggested that a high level of serum indoxyl sulfate may be one of the mechanisms underlying the progression of atherosclerotic lesion, which is the leading cause of cardiovascular event or death in dialysis patients. In this study, we examined retrospectively whether AST-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 25 publications
3
58
2
Order By: Relevance
“…Administration of the oral adsorbent AST-120 before initiating dialysis has been shown to not only improve the survival rate in patients on HD 144,145 but also, delay the onset of HD in patients with CKD. 146 AST-120 is also associated with a reduction in carotid intima media thickness and arterial stiffness in patients with CKD and without diabetes.…”
Section: Inhibition Of Gastrointestinal Absorptionmentioning
confidence: 99%
“…Administration of the oral adsorbent AST-120 before initiating dialysis has been shown to not only improve the survival rate in patients on HD 144,145 but also, delay the onset of HD in patients with CKD. 146 AST-120 is also associated with a reduction in carotid intima media thickness and arterial stiffness in patients with CKD and without diabetes.…”
Section: Inhibition Of Gastrointestinal Absorptionmentioning
confidence: 99%
“…Nakabayashi et al used supplemental symbiotics (probiotic combined with prebiotic) for two weeks and observed significant reductions in p-cresyl sulfate levels and the normalization of bowel habits in hemodialysis patients [88]. Furthermore, AST-120, an oral adsorbent capable of binding solutes and preventing their intestinal absorption represents a type of therapy able to reduce the levels of indoxyl sulfate [89]. In addition, a recent study demonstrated that supplementation with AST 120 appears to improve intestinal barrier, inflammation and oxidative stress of CKD [90].…”
mentioning
confidence: 99%
“…116,136,[150][151][152][153] In CKD patients, AST-120 has been shown to improve estimated creatinine clearance, 154 to delay the progression to ESRD, 155 and to improve survival. 156 Two large-scale trials are currently ongoing testing the role of AST-120 in CKD populations. 157,158 Cardiorenal-protective effects of AST-120 recently have been demonstrated in a small, uncontrolled trial of chronic HF patients with moderate CKD.…”
Section: Heartmentioning
confidence: 99%